Membangun Aplikasi Manajemen Mahasiswa Menggunakan React Vite dan Laravel - Abdillah , Athif Nur; Fakhriza , Naufal; Adritara , Muhammad Zaid Parhan; Saputra , Adji Setyawan; Faizzaki , Nurfaiq; Rosanti , Nurvelly; Ambo , Sitti Nurbaya; Risanty , Rita Dewi; Hendra , Hendra (LPPM Universitas PGRI Argopuro Jember, 2026)
Mastering modern full-stack technology is crucial, yet students often struggle to integrate frontend and backend systems using React Vite and Laravel. This community service program aims to bridge this gap through intensive training titled